Overview of DFIG-Based Wind Turbine Systems in Europe - Seyed-Bouzari, Seyed Ali; Muetze, Annette; Bacher, Johann Peter; Polajžer, Boštjan (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
Doubly-Fed Induction Generators (DFIGs) when used in Wind Turbine Systems (WTS), are typically sized within the 1.5 to 6 MW power range. Currently, DFIG-based systems hold a significant position in the global market, and they are expected to experience substantial growth by 2030.